Meniscal mineralisation in little spotted cats - Rahal, Sheila Canevese [UNESP]; Fillipi, Mauricio G. [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Oliveira, Hugo S. [UNESP]; Teixeira, Carlos Roberto [UNESP]; Teixeira, Rodrigo H.F.; Monteiro, Frederico O.B. (Springer Nature, 2013)
Background: The aim of this study was to evaluate the stifle joints of little spotted cats in captivity using radiographic and CT studies. The hypothesis was that these animals would have meniscal mineralisation that could be detectable by imaging studies. Twelve intact little spotted cats (Leopardus tigrinus), 2 females and 10 males, aged from 1.5 to 11.11 years old and weighing 1.9-3.05 kg were studied. These animals, which were living in the Quinzinho de Barros Municipal Zoo, had no symptoms or known disease processes at the time of the study. The plain radiographs and computed tomography (CT) scans of both stifle joints were performed under general anaesthesia. Sequential transverse images were acquired on a spiral scanner.Results: No signs of articular disease were observed in any of the animals. Radiographically, the meniscal mineralisation was detected as an oval radiopacity in the cranial compartment on the mediolateral projection, located within the area of the medial meniscus. On craniocaudal projection, the mineralisation was more difficult to visualise. In one of the animals, it was not possible to identify the meniscal mineralisation in either of the stifle joints. Using CT, meniscal mineralisation was best identified in the transverse plane images.Conclusions: Meniscal mineralisation appears to be a normal anatomic feature in little spotted cats. © 2013 Rahal et al.; licensee BioMed Central Ltd.
Keywords: Animalia; Leopardus tigrinus